Implementation of Assistance for Victims of Domestic Violence - Kasim, Nur Moh.; Kamba, Sri Nanang Meiske (Universitas Negeri Semarang, 2019)
This research aims to empirically analyses of implementation of counselling towards victims of domestic violence. The research method is descriptive qualitative. The population of this study were women (wives), who were victims of different types of domestic violence at Tabongo Timur Village. Based on the result, there were three pattern implementations of counselling that have been done at Tabonga Timur Village, firstly, providing direction/guidance; secondly, assisting domestic violence victims; and thirdly, establishing domestic violence clinic. The realization of the program of providing counselling of domestic victims at Tabonga Timur Village has not been optimal because the victims are afraid to report, limited fund allocation, inadequate facilities and infrastructure, and both characteristics of victims and factors of domestic violence are various.